Primeron Reforms in a Second-Best Ambiguous Environment : A Case for Gradualism - Erbas, S. (IMF Working Papers; Working Paper ;, 2002)
Ambiguity, as opposed to uncertainty, reflects lack of sufficient information about distribution and payoffs of infrequent events. Reforms are infrequent events, undertaken in ambiguous second-best environments where bad reform outcomes are feasible. A general case for the gradualist reform strategy is that it may pay to defer some reforms until relevant information about possible reform outcomes and associated probabilities is revealed, and ambiguity is reduced over time. Gradualism may dominate the big bang strategy, if some of the reforms in a reform sequence are not sure bets and waiting costs do not dominate reversal costs under some information sets forthcoming over time. The relation to Ellsberg's Paradox is discussed. Some cases for and against gradualism are reviewed.